Cortical activation and language task difficulty in aphasia - Fridriksson, Julius (2005)
BACKGROUND: Previous research using functional MRI (fMRI) suggests changes in cortical activation as a function of increased task difficulty. This relationship has not been explored in persons with aphasia even though it may have significant implications for pre- and post-treatment interpretation of fMRI data. AIMS: The purpose of this exploratory study was to investigate the relationship between changes in language task difficulty and cortical activation in persons with aphasia. METHODS & PROCEDURES: Four persons with chronic anomic or Broca’s aphasia and four matched control participants underwent fMRI while performing a picture–word matching task. OUTCOMES & RESULTS: Compared to the more difficult task condition, all participants performed with greater accuracy on the easier condition. Moreover, greater mean blood oxygenated level dependent (BOLD) signal intensity and area recruitment were noted during the more difficult condition for three out of four persons with aphasia as well as three of the four controls. The increase in cortical activity was mainly noted in the superior temporal and posterior inferior frontal lobes. CONCLUSIONS: The present findings mirror those found in previous studies of normal subjects in that cortical activation increased in parallel to task difficulty for most of our participants. It is unclear what mechanism accounts for this effect; this phenomenon might need to be considered in future fMRI studies of neural plasticity associated with aphasia treatment.